Analysis of the Influence of Islamic Religious Education on Quarter Life Crisis Among the Young Generation - Rahmadani, M. Rifki; Sukino, Sukino; Sumin, Sumin (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This study aims to analyze the influence of social competence on the learning motivation of Muslim students in the Physical Education Study Program at IKIP PGRI Pontianak. Social competence, which includes communication skills, cooperation, and emotional management, is considered to play an important role in creating a conducive learning environment and supporting academic achievement. The research method used is a quantitative approach with Structural Equation Modeling (SEM) analysis using Smart PLS software. The results of the study show that social competence has a positive and significant effect on learning motivation. These findings emphasize the importance of developing social competence as an integral part of higher education curricula, especially in study programs based on Islamic values.